Ribosomal Protein S6 Phosphorylation Is Involved in Novelty-Induced Locomotion, Synaptic Plasticity and mRNA Translation - Puighermanal, Emma; Biever, Anne; Pascoli, Vincent; Melser, Su; Pratlong, Marine; Cutando, Laura; Rialle, Stephanie; Severac, Dany; Boubaker-Vitre, Jihane; Meyuhas, Oded; Marsicano, Giovanni; Lüscher, Christian; et al. (Frontiers in Molecular Neuroscience, 2017)
The phosphorylation of the ribosomal protein S6 (rpS6) is widely used to track neuronal activity. Although it is generally assumed that rpS6 phosphorylation has a stimulatory effect on global protein synthesis in neurons, its exact biological function remains unknown. By using a phospho-deficient rpS6 knockin mouse model, we directly tested the role of phospho-rpS6 in mRNA translation, plasticity, and behavior. The analysis of multiple brain areas shows for the first time that, in neurons, phospho-rpS6 is dispensable for overall protein synthesis. Instead, we found that phospho-rpS6 controls the translation of a subset of mRNAs in a specific brain region, the nucleus accumbens (Acb), but not in the dorsal striatum. We further show that rpS6 phospho-mutant mice display altered long-term potentiation in the Acb and enhanced novelty-induced locomotion. Collectively, our findings suggest a previously unappreciated role of phospho-rpS6 in the physiology of the Acb, through the translation of a selective subclass of mRNAs, rather than the regulation of general protein synthesis.